Dampak Budaya Perusahaan terhadap Kinerja dan Inovasi Karyawan - Salsabila Zhafirah Ramadhani; Haliza Widiya Utami; Ikhsan Muhamad Mudjenan; Wahu Imam Rajani; Della Amelia (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Using a Systematic Literature Review (SLR) approach, which conforms to the PRISMA protocol, this study investigates the influence of corporate culture on employee performance and innovation. As an important component, corporate culture influences the nature of the organization and creates a pleasant working environment. The analysis shows that a strong organizational culture increases employee productivity, motivation, and engagement. This finding is supported by many studies that found a relationship between organizational culture and employee satisfaction and achievement of company goals. Conversely, corporate culture is essential to encourage employees to be innovative. This study found that the role of transformational leadership and organizational commitment in strengthening the relationship between organizational culture and innovation, and that an environment that supports creativity and risk-taking can help innovative behavior, especially in industry 4.0. Overall, this study emphasizes that corporate culture is essential as a strategic part of contemporary management. To create a productive and innovative organization, it is important to implement a corporate culture that supports effective cooperation. The results suggest that company leaders can use these findings to maximize the potential of their human resources.